2006
DOI: 10.2514/1.16746
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Free Falling Pararotor

Abstract: The pararotor is a decelerator device based on the autorotation of a rotating wing. When it is dropped, it generates an aerodynamic force parallel to the main motion direction, acting as a decelerating force. In this paper, the rotational motion equations are shown for the vertical flight without any lateral wind component and some simplifying assumptions are introduced to obtain analytic solutions of the motion. First, the equilibrium state is obtained as a function of the main parameters. Then the equilibriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…With the objective of comparing the case where k 3i is different from zero with the case where k 3i is zero, the same aerodynamic model used in previous work [16] was adopted. The fact of considering the parameter & 31 implies the introduction of a great complexity because the number of terms of system of equations became extremely large.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…With the objective of comparing the case where k 3i is different from zero with the case where k 3i is zero, the same aerodynamic model used in previous work [16] was adopted. The fact of considering the parameter & 31 implies the introduction of a great complexity because the number of terms of system of equations became extremely large.…”
Section: Methodsmentioning
confidence: 99%
“…The induced velocity v t was not directly included in the model, following similar assumptions of former studies [16]. Other studies [22] indicated that a real low-aspect-ratio rotary wing shows an induced power correction factor K of about 2 or greater.…”
Section: A Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations